2001
DOI: 10.1063/1.1377891
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of classically forbidden electronic transitions in semiclassical trajectory surface hopping calculations

Abstract: A family of four weakly coupled electronically nonadiabatic bimolecular model photochemical systems is presented. Fully converged quantum mechanical calculations with up to 25 269 basis functions were performed for full-dimensional atom-diatom collisions to determine the accurate scattering dynamics for each of the four systems. The quantum mechanical probabilities for electronically nonadiabatic reaction and for nonreactive electronic deexcitation vary from 10 Ϫ1 to 10 Ϫ5 . Tully's fewest-switches ͑TFS͒ semic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
125
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 46 publications
1
125
0
Order By: Relevance
“…Using the þ, À, and cV and prescriptions, the trajectory does not change electronic states at a frustrated hop, which violates the self-consistency argument originally 107 used to justify the TFS hopping probability, and numerical studies 75,128 have shown that using these prescriptions leads to inaccurate electronic-state trajectory distributions. The fewest-switches with time-uncertainty (FSTU) method 128 has been developed to correct this deficiency.…”
Section: Semiclassical Trajectory Methodsmentioning
confidence: 93%
See 4 more Smart Citations
“…Using the þ, À, and cV and prescriptions, the trajectory does not change electronic states at a frustrated hop, which violates the self-consistency argument originally 107 used to justify the TFS hopping probability, and numerical studies 75,128 have shown that using these prescriptions leads to inaccurate electronic-state trajectory distributions. The fewest-switches with time-uncertainty (FSTU) method 128 has been developed to correct this deficiency.…”
Section: Semiclassical Trajectory Methodsmentioning
confidence: 93%
“…75 The TFS algorithm may predict a nonzero hopping probability to a higher-energy electronic state in regions where the nuclear momentum is insufficient to allow for an energy adjustment that will conserve total energy. For example, due to tunneling, quantum mechanical particles have some probability density in regions of phase space that are classically forbidden.…”
Section: Semiclassical Trajectory Methodsmentioning
confidence: 99%
See 3 more Smart Citations